Minimum load shedding for improving total loss during line outage contingency using evolutionary programming technique / Wan Nur Eliana Afif Wan Afandie - Wan Afandie, Wan Nur Eliana Afif (2010)
This project presents a methodology for solving minimum load shedding problem during line contingency by using Evolutionary Programming (EP) technique in order to minimize the losses and maximize the minimum voltage in the power system. This case study has been developed through the Evolutionary Programming (EP) technique using MATLAB software. This study tested two fitness functions. They are the maximization of minimum voltage and the total losses minimization in a power system. Comparison in the results obtained was made in order to determine the best fitness function to be used in solving the minimum load shedding problem. The proposed technique was tested on the IEEE 30-bus reliability test system.